Factors affecting recreation and leisure participation among youth post-COVID-19 in Mopani District of South Africa - Mukhuba, Fulufhelo Ronaldo (My University, 2026)
The COVID-19 pandemic changed people's way of life drastically across the globe. This highly contagious viral disease was considered a pandemic by the World Health Organisation. Even when COVID-19 had detrimental effects globally, in some parts of the world, people saw recreation and leisure activities as a means to unite society. Therefore, this study aims to investigate the factors that affect recreation and leisure participation among youth in the Mopani District following the COVID-19 pandemic. This proposed aim was achieved through a qualitative research approach, which adopted an exploratory research design. A convenience sampling technique was used to sample 10 participants in the Mopani District. Through qualitative methods, data were collected via semi-structured interviews and analysed using a thematic analysis. Four themes were identified from the data: Shift toward Solo or Small-Group Outdoor Activities, Barriers to participation, Recreation and leisure educational initiatives, and Perceived importance of recreation and leisure. The findings show a clear shift toward solo and home-based activities caused by psychological and practical barriers such as anxiety, financial constraints, inadequate infrastructure, and gender-specific limitations. Despite these obstacles, the study highlights a growing recognition of the importance of leisure for promoting well-being, social connection, and personal development. The proposed recommendations offer a practical way to enhance youth access to safe, inclusive, and mentally beneficial recreational activities in the post-pandemic era.
MPH
Department of Public Health
Keywords: Activities; UCTD; COVID-19; Leisure; Recreation; Youth